An overview on concrete carbonation in the context of eco-efficient - Pacheco-Torgal, F. (2012)
Carbonation is a major cause of concrete structures deterioration leading to expensive maintenance and conservation operations. The eco-efficient construction agenda favours the increase of the use of supplementary cementing materials (SCMs) to reduce Portland cement’s consumption and also the use of recycled aggregates concrete (RAC) in order to reduce the consumption of primary aggregates and to avoid landfill disposal of concrete waste. There is a wide range of literature published on the field of concrete carbonation related to the use of SCMs and/or RCA. However, the different conditions used by different authors limit comparison and in some cases contradictory findings are noticed. Besides, since most investigations are based on the use of the phenolphthalein indicator, which provides a poor estimate of the real concrete carbonation depth, there is a high probability that past researches could have underestimate the corrosion potential associated to concrete carbonation. This paper reviews current knowledge on concrete carbonation addressing carbonation depth’s measurement, the use of SCMs and or RAC.